Multiply the first term in the left parentheses by each term in the right parentheses. Then multiply the second term in the left by each in the right. Do the same with the third term in the left parentheses.
=(6x3 - 3x2 + 5x + 9)(7x + 9)
=(6x3*7x)+(6x3*9)-(3x2*7x)-(3x2*9)+(5x*7x)+(5x*9)+(9*7x)+(9*9)
Start multiplying each set
Remember when multiplying exponents, you add them
=(42x4)+(54x3)-(21x3)-(27x2)+(35x2)+(45x)+(63x)+81
Combine any like terms
=42x4+(54x3-21x3)-(27x2+35x2)+(45x+63x)+81
=42x4+33x3+8x2+108x+81
The answer is
A) 42x4+33x3+8x2+108x+81
Hope this helps! :)